Thermal conductivity of graphene nanoribbons - Guo, Zhixin; Zhang, Dier; Gong, Xin-Gao (Applied physics letters, 2009)
We have investigated the thermal conductivity of graphene nanoribbons (GNRs) with different edge shapes as a function of length, width, and strain using nonequilibrium molecular dynamics method. The initial GNR for the functional variations has dimensions of 2 × 11